Intraperitoneal rectal perforation presenting as fetal ascites – a rare occurrence (Indian Journal of Case Reports, 2016)
Spontaneous perforation of the rectum presenting as fetal ascites is an extremely rare occurrence. We report the case of an infant where antenatally detected fetal ascites was attributable to intraperitoneal rectal perforation. Investigations directed to identify common causes of this condition did not reveal any aetiology. Patient underwent surgical colostomy formation on day two of life, which was reversed at six weeks of age. We suggest that meconium ascites and peritonitis should be considered as differential diagnoses in fetuses with ascites and, if the neonate requires a laparotomy, the rectal area should be thoroughly inspected to exclude this entity.